Pharmacy Technicians in Clinical Support Services: Evaluating Their Impact on Medication Accuracy and Patient Care Outcomes - Alrehaili, Ziyad Jameel; Almutairi, Naif Habeeb; Almutairi, Abdulaziz Fahid; Aldowimar, Malek Abdullah; Almutairi, Eid Safer; Alhilali, Ayman Mohammed; Aljehani, Mohammed Suliman (Journal of Posthumanism, 2023)
Pharmacy technicians play an increasingly critical role in modern healthcare systems as clinical demands on pharmacists intensify. This systematic review evaluates the impact of pharmacy technicians on medication accuracy, safety, workflow efficiency, and patient care outcomes across hospital, ambulatory, and community pharmacy settings. Recent evidence demonstrates that well-trained pharmacy technicians contribute significantly to reducing dispensing errors, enhancing medication preparation accuracy, and supporting verification processes, thereby improving overall medication safety. Their integration into advanced clinical support tasks—such as tech-check-tech verification, sterile compounding, medication history collection, and digital medication management—has enabled pharmacists to focus more on direct patient care activities. The review also highlights the influence of technician roles on patient wait times, adherence, and overall satisfaction with pharmacy services. Despite promising outcomes, challenges remain regarding variability in training, regulatory inconsistencies, and differences in scope of practice across countries. The study concludes that expanding the role of pharmacy technicians within a structured regulatory and competency framework can substantially enhance medication accuracy and patient outcomes, especially as healthcare systems continue transitioning toward team-based, technology-enabled models of pharmaceutical care.